Big Data Research in Italy: A Perspective. (June 2016) - Bergamaschi, Sonia; Carlini, Emanuele; Ceci, Michelangelo; Furletti, Barbara; Giannotti, Fosca; Malerba, Donato; Mezzanzanica, Mario; Monreale, Anna; Pasi, Gabriella; Pedreschi, Dino; Perego, Raffele; Ruggieri, Salvatore
ABSTRACT: The aim of this article is to synthetically describe the research projects that a selection of Italian universities is undertaking in the context of big data. Far from being exhaustive, this article has the objective of offering a sample of distinct applications that address the issue of managing huge amounts of data in Italy, collected in relation to diverse domains.